2020
DOI: 10.1111/imj.14963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on an Australian intensive care unit: lessons learned from South Australia

Abstract: The scale of the COVID‐19 pandemic represents unprecedented challenges to healthcare systems. We describe a cohort of 18 critically ill COVID‐19 patients – to our knowledge the highest number, in a single intensive care unit in Australia. We discuss the complex challenges and dynamic solutions that concern an intensive care unit pandemic response. Acting as the State's COVID‐19 referral hospital, we provide local insights to consider alongside national guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 4 publications
1
12
2
Order By: Relevance
“…A study in Michigan of 141 patients found a mortality frequency of 40.4% (57) at 30 days of admission [ 33 ]. In Australia, a study of 18 patients admitted reported death of four (22%) patients in the ICU [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Michigan of 141 patients found a mortality frequency of 40.4% (57) at 30 days of admission [ 33 ]. In Australia, a study of 18 patients admitted reported death of four (22%) patients in the ICU [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are supported by previous studies where although the incidence of a pneumothorax was low (0.3%) in admitted COVID-19 patients, this incidence increased up to 23.8% in those requiring MV. In addition to this, the time interval between a pneumothorax diagnosis and admission had been observed to be around 9 to 19.6 days whereas the time between MV initiation and a pneumothorax was noted to be 5.4 days [ 32 , 33 , 34 , 35 ]. Although a COVID-19-related pneumothorax can be a result of COVID-19-induced inflammation and immune dysregulation, our findings suggest an association between the use of invasive mechanical ventilation and a pneumothorax and encourage further studies to be performed to assess this association.…”
Section: Discussionmentioning
confidence: 99%
“…25 Despite small numbers, our ICU mortality figures are higher than reported in other Australian ICU studies. 20,26 Our case fatality rate of 1.8% compares favourably to the Australian wide rate of 3.0%. 2 We hypothesise that the comparatively lower mortality rate seen in this study is reflective of several factors.…”
Section: Covid-19 Clinical Characteristicsmentioning
confidence: 43%